Kirkehistorie mellom det globale og det nasjonale - Rasmussen, Tarald (Dansk teologisk tidsskrift, 2013)
Resumé The new Danish two volume Church History aims at an integrationof a global and a national perspective. The article discussesthe handbook with a main focus on the theoretical perspectives appliedin the text, including aspects like gender, confessional cultures and acomparative approach to Church History.